FENOMENA ELITE CAPTURE DALAM PENGELOLAAN BADAN USAHA MILIK DESA (BUMDES) - Syahran Firdaus (Politika: Jurnal Ilmu Politik, 2018)
Village independence is one of the main focuses to achieve the welfare of rural communities. One of the implications of the village independence agenda is the presence of BUMDes as a rural institution to perform the function of empowering and improving the welfare of the community. However, the presence of BUMDes can lead to new problems: the emergence of an elite presence dominates BUMDes. One of the phenomena that can happen is Elite Capture. Elite capture is an elite hijacking of management spaces for personal or group interests. The object of this research is BUMDes Argosari located in Pulosari Village, Pemalang Regency. This study focuses on investigating elite capture phenomena by looking at the strategy of empowering elite power by using John Gaventa's power cube theory in hijacking the management of BUMDes at each stage of its management. Stages of management are divided into four stages of agenda setting, implementation, monitoring, and evaluation. Each stage is analyzed by the elite hijacking actions so that later will get a comprehensive picture of capturing behavior conducted by the elite. This research uses qualitative method with case study approach. Village Head and Chairman of BPD are two powerful actors who are very influential in the management of Argosari BUMDes. Both actors are often contested in the context of BUMDes management. However, during the process of running the village management is a very dominant actors that often plow each stage of management BUMDes. Some of the factors that make the village strong enough position in internal BUMDes is a very strong relationship with outside parties, both the private and supradesa government. In addition, village heads are also able to build high compliance against the internal ranks of BUMDes so that internal BUMDes is very dependent on the figure of village head. While the Chairman of BPD, only optimal in the realm of supervision only. The role and power possessed by the head of BPD is not enough to offset the power of the village head in the management of BUMDes. Chairman of the BPD to fight in the form of reprimands either verbally or in writing to the internal BUMDes and Kades as advisor BUMDes and establish relationships with groups that also cons with the leadership of village.